KORELASI POLA PEMBERIAN MAKAN DAN RIWAYAT ASI EKSLUSIF DENGAN STATUS GIZI BERDASARKAN COMPOSITE INDEX OF ANTHROPOMETRIC FAILURE (CIAF) PADA ANAK 24-59 BULAN - Utami, Utami; Sianipar, Kandace; Ramli, Kamrianti; Siddiq, Muhammad Nuzul Azhim Ash (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The Composite Index Of Anthropometric Failure (CIAF) or composite of malnutrition or growth failure in children under five is a picture of the problem of child malnutrition from the past to the present. Kampar Health Center is the highest health center for nutritional problems in toddlers in Kampar Regency. The purpose of the study was to determine the correlation of feeding patterns and exclusive breastfeeding history with nutritional status based on the composite index of anthropometric failure (CIAF) in children 24-59 months. The research design used in this study was cross sectional. The research was conducted at the Kampar Health Center. The research was conducted in August 2022. The sample amounted to 288 people. The sampling technique used in this study was purposive sampling. Data analysis was carried out univariate and bivariate. The results showed there was a relationship between feeding patterns (p value: 0.004) and exclusive breastfeeding history (p value: 0.032) to nutritional status in toddlers. It is suggested to the Puskesmas that it is necessary to increase counseling by health workers to mothers about proper and correct feeding patterns according to the age of the child so that they can meet adequate intake and optimal nutritional status.Keywords: Exclusive breastfeeding, toddlers, feeding patterns.